The threshold ambient temperature for the use of pre-cooling to improve cycling time trial performance - Steve H. Faulkner; Iris Broekhuijzen; Margherita Raccuglia; Maarten Hupperets; Simon Hodder; George Havenith (2019)
Purpose. Cycling time trial performance can be compromised by moderate to high ambient temperatures. It has become commonplace to implement pre-cooling prior to competition to alleviate this performance decline. However, little is known about the ambient temperature threshold above which pre-cooling becomes an effective strategy for enhancing endurance performance. It was the aim of this study to investigate the effect of pre-cooling in different environmental temperatures on time trial performance. Methods. Trained cyclists completed two time trials with (COLD) and without (CON) pre-cooling using an ice-vest and sleeves ensemble in ambient temperatures of 24˚C, 27˚C and 35˚C. Results. Time trial performance faster following COLD in both 35˚C (6.2%) and 27˚C (2.6%; both P